Religion as a Social Sign: Sharia Identity in Muslim Consumer Culture - Aisyah Putri Berliana Machfudz (Journal of Educational Management Research, 2026)
This study aims to examine religion as a social sign within contemporary Muslim consumer culture, focusing on how Sharia identity is constructed and communicated through the consumption of halal-labeled commodities. Using a qualitative descriptive approach, the research employs digital observation and a sociology of consumption perspective to analyze the commodification of religious symbols within capitalist market dynamics. The findings indicate that the consumption of Sharia products extends beyond expressions of personal piety and functions as a strategy of social distinction and identity performance. Religious symbols embedded in commodities serve as markers of lifestyle, status, and group belonging, transforming spiritual values into marketable and exchangeable goods. This process demonstrates how religious identity is increasingly shaped through consumption practices that align with neoliberal cultural logic. The study implies that the commodification of religion has redefined the relationship between faith, identity, and the market. It highlights the growing integration of religious values into consumer culture and contributes to a deeper understanding of how religion operates as both a symbolic resource and an economic asset in contemporary society.